Recompondo Medéia: entre sigilos, dispositivos e produções discursivas de gênero nos processos judiciais atravessados por alegações de Alienação Parental - BATALHA, Glaucia Fernanda Oliveira Martins (2024)
Law 12,318/2010, currently in force, establishes the civil offense known as Parental Alienation. According to its legal framework, Article 2 defines Parental Alienation (PA) as interference in the psychological development of a child or adolescent, promoted or induced by one of the parents, grandparents, or others who hold authority, custody, or supervision over the child or adolescent, aimed at alienating them from the other parent or undermining the establishment or maintenance of bonds with them. In this context, the present research seeks to develop a critical analysis to complexify and challenge the crystallized and normative understanding of Parental Alienation through the examination of 22 (twenty-two) legal cases and 14 (fourteen) hearings accessed between 2022 and 2023.Grounded in a qualitative methodology with a socio- anthropological and legal approach inspired by ethnography, the empirical field of this study is conceptualized as "archive-villages," that is, judicial cases involving reports of Parental Alienation, permeated by the confidentiality of justice. The research adopts gender as a central analytical category. This thesis investigates the intersection of gender and Parental Alienation, encompassing discourse, knowledge, power, motherhood, parenthood, and family. Judicial records, as they categorize the "alienator," become data that reveal the discursive production circulating and diffusing within the legal field. Such discourse tends to (re)produce gender asymmetries, rooted in gendered and cisheteronormative roles and mythological constructs that shape legal interpretations and practices within the justice system. These constructs often stereotype parental conflicts, positioning women as "alienating mothers" and men as "fathers victimized by alienation." This perspective generates unequal treatment of men and women under Law 12,318/2010 when accused of alienation, as the justice system's interpretation and response vary according to the accused's gender.In this regard, legal provisions, coupled with social and juridical practices, shape perceptions, influence behaviors, classify subjects, reinforce social representations and expectations, (re)produce gender stereotypes, and uphold normative models of motherhood, fatherhood, parenthood, and family.